Phylogeny, Diversification Rate, and Divergence Time of Agave sensu lato (Asparagaceae), a Group of Recent Origin in the Process of Diversification - Jiménez-Barron, Ofelia; García-Sandoval, Ricardo; Magallón, Susana; García-Mendoza, Abisaí; Nieto-Sotelo, Jorge; Aguirre-Planter, Erika; Eguiarte, Luis E. (Frontiers in Plant Science, 2020)
Agave sensu lato is one of the most diverse and complex genera of the Asparagaceae, with more than 250 species. The morphological, ecological and evolutionary diversity of the group has complicated its taxonomical study. We conducted phylogenetic analyses of DNA sequence data to reconstruct the phylogenetic relationships of the Agave genus. We included 107 species of the Asparagaceae family from which 83 correspond to Agave sensu lato clade (Agave sensu stricto + Polianthes + Manfreda and Prochnyanthes, which together represent 30% of the genus) and as outgroups the genera Dasylirion, Hesperoyucca, Chlorogalum, Camassia, Hesperaloe, Yucca, Beschorneria, and Furcraea, in order to estimate the age and propose the history of their diversification. Previous studies postulated the relevance of the Miocene in the speciation rates of the agaves, as well as the relevance of the type of inflorescence in its diversification. However, these assertions have not been well supported. The analysis of chloroplast regions resulted in low resolution, which could be consequence of the few variable sites. On the other hand, the ITS implemented in our analysis ensued in higher resolution and better support values. Our phylogenetic analyses recovered five groups; one is the Striatae group, which is the sister group to Agave sensu stricto clade. Within this clade we found three main groups with high support; these groups are not related with previous morphological proposals. We also analyzed the dates of origin and diversifications rates. A Bayesian analysis of macroevolutionary mixtures indicated two significant shifts, the first was identified at 6.18 Ma, where the speciation rate increased to 4.10 species/Mya, this shift occurred during the late Miocene period, characterized by the emergence of arid biomes in North America. The second was identified at a stem age of 2.68 Ma where the speciation rate increased to 6.04 species/Mya. Concerning the ancestral reconstruction state of the inflorescence type in the Agave sensu stricto clade, the spike inflorescence character was predominant in the early-diverging groups, while late-diverging groups present panicle inflorescences as the predominant character, and higher speciation rates.